Islam dan Lembaga Negara: Perspektif Tafsir Maudhu'i - El-Hakim, Abdul Halim; Kurniawan, Ahmad Arif; Muhyi, Asep Abdul; Gultom, Ayuni Wulan Sari (Melati Institute, 2024)
Islam and state institutions have long been the focus of academic research and popular discussion. Islam is one of the major world faiths, and as such, it has a big impact on the social, legal, and political environments of many countries, especially those where the majority population is Muslim. This article examines the complex relationships between Islam and state institutions, looking at how Islamic values influence the creation and application of laws, regulations, and governmental frameworks. It explores the difficulties of balancing Islamic principles with contemporary state governance through a comparative study of various strategies used by nations with a majority of Muslims population. It also addresses the opportunities and difficulties that arise from the interaction of Islam with state institutions, emphasizing the need to strike a balance between religious observance and democratic ideals as well as the consequences for social justice, human rights, and sustainable development. This essay seeks to advance knowledge of the changing dynamic between Islam and state institutions in modern countries by clarifying these nuances.